Response of aerobic rice (Oryza sativa L.) to seed rate and inter-row spacing, Gezira State, Sudan - M. A. Elhassan, Osama; M. Hamid, Ishraga (Gezira Journal of Agricultural Science, 2021)
Field experiments were conducted for two consecutive seasons (2013/14 and 2014/15) at the Gezira Research Station Farm, Wad Medani, Sudan under irrigation condition. A randomized complete block design with four replicates was used. Treatments were arranged in a factorial combination of four inter-row spacing (15, 20, 25 and 30 cm) and five seed rates (59, 71, 83, 95 and 107 kg/ha). Data collected consisted of growth attributes, grain yield and yield components. Data collected were subjected to standard analysis of variance procedure. The results showed that seed rate, inter-row spacing and their interaction exhibited highly significant differences in grain yield and yield components. The highest grain yield was obtained by the seed rate of 95 kg/ha and 15 cm inter-row spacing in both seasons and the combined analysis. To obtain high grain yield of aerobic rice under Gezira conditions, 95 kg/ha seed rate and inter-row spacing of 15 cm is recommended to be used.